Europeanness: a path to unity within the European Union - Ryszard Piasecki; Jan Woroniecki (Comparative Economic Research. Central and Eastern Europe, 2016)
The postwar experience has shown that the implanting of European consciousness, or Europeanness, calls for coordinated efforts among the European institutions, national states, and NGOs. Such consciousness, a key pillar of the European integration, is necessary for the EU to effectively function and motivate member states' - also the EU's - citizens. And yet European institutions and EU governments show little interest in promoting the formation of this European consciousness. Pro-European social movements are weak, while anti- European ones gain strength. This désintéressement of the EU countries probably results from the conviction that the goal has been reached and that there is no more need for a widespread pro-European education of their societies. However analysis of the problem, and in particular of the interaction between European and national identities, shows that this is not the case. We fear that this lack of proactive measures mobilizing EU citizens to keep on struggling for a common Europe will lead to the erosion of existing achievements of integration within the EU, and undermine European values. It may threaten the future of the EU, which is not an ordinary integration grouping but a great peaceful, civilizational, social and economic project. Our hypothesis - positively verified in this article - is that the promotion of Europeanness in the EU societies is urgently needed to maintain the unity (and even membership) of the Union, and to avert trends unfavorable for all of Europe and therefore for the West as a whole.
Keywords: 330; European Union; integration; human dimension; European education